(3EOGQI GdeMGaX GdGSJKeGQjI (B/s - (3Bd THjH, OQjO cGeds ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2010)
(3ebOeI aj GdeMGaX GdGSJKeGQjI , fXQjI h GOGQI GdeMaXI GdGSJKeGQjI , GdYGFO h GdeNGWQ , bjGS GdYGFO h GdeNGWQ aj GdeMaXI , JMdjd HjFI GdGSJKeGQGJ aj GdeMaXI GdGSJKeGQjI , JMdjd GdeMaXI GdGSJKeGQjI , feGPL GdeMGaX GdGSJKeGQjI h CNjQG Jbjje COGA GdeMGaX GdGSJKeJQjI (B.s
(3eQGLY U(B.221((3GbJfGAGJ (B2014 10(3f(B)s
Keywords: (3GdGSJKeGQ GdeGdjs; (3GdGSJKeGQGJs; (3GdGbJUGO GdeGdjs